Thermal capacity of new nanodimensional cobalt-cuprate-manganite LaLi2CoCuMnO6 and nickelite-cuprate-manganite LaLi2NiCuMnO6 in the interval of 298.15–673 K and their thermodynamic properties - Kassenov, B.K.; Kassenova, Sh.B.; Sagintaeva, Zh.I.; Kuanyshbekov, E.E.; Kopylov, N.I. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The specific thermal capacities of our new obtained nanodimensional cobalt-cuprate-manganite and nickelitecupratemanganite of lanthanum and lithium of structures LaLi2CoCuMnO6 and LaLi2NiCuMnO6 were first studied with the method of a dynamic calorimetry in the interval of temperatures of 298.15–673 K. Their mole thermal capacities were calculated from specific thermal capacities. It was established that LaLi2CoCuMnO6 at 398 K and LaLi2NiCuMnO6 at 373 K and 573 K were subjected to II-type phase transitions. Based on temperature of phase transitions the equations of temperature dependence of thermal capacity were set up. All obtained experimental and calculated data were processed strictly with methods of mathematical statistics. The mean square deviations were measured for average values of specific thermal capacities, as well as random components of an error for mole thermal capacities. The standard entropies of the studied compounds were calculated with method of ionic increments. Referring to the experimental data on thermal capacities and calculated values of standard entropies in the interval of 298.15–675 with step through 50 K the temperature dependences of an enthalpy of Нº(Т)–Нº(298.15), entropy of Sº(T) and the specified thermodynamic potential Фхх(Т) were calculated.
298,15–673 К аралығында жаңа наномөлшерлі кобальт-купрат-манганиті LaLi2CoCuMnO6 мен LaLi2NiCuMnO6 никелит-купрат-манганитінің жылусыйымдылығы жəне олардың термодинамикалық қасиеттері
Теплоемкость новых наноразмерных кобальто-купрато-манганита LaLi2CoCuMnO6 и никелито-купрато-манганита LaLi2NiCuMnO6 в интервале 298,15–673 К и их термодинамические свойства
Keywords: thermodynamics; cobalt; nickelite; cuprate; manganite; thermal capacity; calorimetry; lanthanum; lithium